Environmental education in the context of rural education: A study in a public school in the municipality of Upanema – RN - Aquino, Josiel Medeiros de; Castro, Késia Kelly Vieira de (Revista Hipótese, 2023)
Environmental Education has been a topic of discussion among various national and international organizations in recent years, addressing the relationship between the environment and society. This article aims to comprehend the perception of students at a primary school concerning Environmental Education. This institution is situated in the São Manoel II agrarian reform settlement in the municipality of Upanema, Rio Grande do Norte. Based on the research results, it is possible to identify information that provides a unique perspective on Environmental Education. This underscores the need for discussions and broadens the possibilities of approach within the rural school context.
Keywords: Environmental Education; Rural Education; Agrarian reform settlements